Fundamentals of management - Donnelly, James H.; Gibson, James L.; Ivancevich, John M. (Homewood, Illinois : BPI and Irwin, 1987)
This is a quality work on management for students and professionals.
Includes bibliographical references and index.
ucj 17/01/2019
Loans
Keywords: Management